Effect of a physical activity intervention on lower body bone health in childhood cancer survivors: A randomized controlled trial (SURfit). Issue 2 (26th August 2022) - Jung, Ruedi; Zürcher, Simeon J.; Schindera, Christina; Eser, Prisca; Meier, Christian; Schai, Anna; Braun, Julia; Deng, Wei Hai; Hebestreit, Helge; Neuhaus, Cornelia; Schaeff, Jonathan; Rueegg, Corina S.; et al.
Abstract: It remains controversial whether physical activity promotes bone health in childhood cancer survivors (CCS). We aimed to assess the effect of a one‐year general exercise intervention on lower body bone parameters of CCS. CCS ≥16 years at enrollment, <16 years at diagnosis and ≥5 years in remission were identified from the national Childhood Cancer Registry. Participants randomized to the intervention group were asked to perform an additional ≥2.5 hours of intense physical activity/week, controls continued exercise as usual. Bone health was assessed as a secondary trial endpoint at baseline and after 12‐months. We measured tibia bone mineral density (BMD) and morphology by peripheral quantitative computed tomography and lumbar spine, hip and femoral neck BMD by dual‐energy x‐ray absorptiometry. We performed intention‐to‐treat, per protocol, and an explorative subgroup analyses looking at low BMD using multiple linear regressions. One hundred fifty‐one survivors (44% females, 7.5 ± 4.9 years at diagnosis, 30.4 ± 8.6 years at baseline) were included. Intention‐to‐treat analysis revealed no differences in changes between the intervention and control group. Per protocol analyses showed evidence for an improvement in femoral neck and trabecular BMD between 1.5% and 1.8% more in participants being compliant with the exercise program. Trabecular BMD increased 2.8% more in survivors of the intervention group with BMD z‐score ≤−1 compared to those starting at z‐score >−1. A nonstandardized personalized exercise programs might not be specific enough to promote bone health in CCS, although those compliant and those most in need may benefit. Future trials should include bone stimulating exercise programs targeting risk groups with reduced bone health and motivational features to maximize compliance. Abstract : What's new? Survivors of childhood cancer have increased vulnerability later in life to decreased bone mineral density (BMD) and fractures. Here, the authors tested whether a one‐year exercise program could help improve lower‐body bone health among 151 cancer survivors, age 16 and up. Those randomized to the exercise group performed an additional 2.5 hours of intense physical activity each week, while those in the control group continued their usual exercise habits. Bone mineral density was measured in the lumbar spine, hip, femoral neck and tibia. After 12 months, the researchers found no statistically or clinically significant difference between the two groups.